Technology acceptance among micro-entrepreneurs in marginalized social strata: The case of social innovation in Bangladesh - Rahman, Syed Abidur; Taghizadeh, Seyedeh Khadijeh; Ramayah, T.; Alam, Mirza Mohammad Didarul (Elsevier Inc., 2017)
Technology adoption by the marginalized community is indeed an important issue in global poverty reduction.To realize it, this paper contributes by doing an empirical test of the technology acceptance model, among st those users typically always deprived in the existing social structure. Firstly, the study aims to examine the influence of Technology Readiness Index (TRI) 2.0′s four indicators (optimism, innovativeness, discomfort and insecurity) on bKash entrepreneurs' perceived ease of use (PEOU) and perceived usefulness (PU) of bKash technology.Secondly, it aims to investigate the effect of ‘bKash’ entrepreneurs' PEOU and PU on their well-being.A total of 360 usable data were collected from the bKash agents in Bangladesh.We employed SEM-PLS3.0 for data analysis.The results indicate that optimism and innovativeness strongly drive perceived ease of use and perceived usefulness.Subjective well-being was found to be strongly predicted by perceived ease of use and perceived usefulness.The study indicates that poor people are somewhat ready to use and accept technology that leads to a sense of well-being.Bringing together the concept of subjective well-being with TRI and Technology Acceptance Model (TAM) is this paper's contribution to the knowledge domain.